Assessment of respiratory mechanics with forced oscillations in healthy newborns. Issue 4 (25th August 2014) - Hantos, Zoltán; Czövek, Dorottya; Gyurkovits, Zita; Szabó, Hajnalka; Maár, Balázs A.; Radics, Bence; Virág, Katalin; Makan, Gergely; Orvos, Hajnalka; Gingl, Zoltán; Sly, Peter D.
Summary: Background: Lung function data in healthy newborn infants are scarce largely due to lack of suitable techniques, although data for developmental and prenatal exposure studies are much needed. We have modified the forced oscillation technique (FOT) for the measurement of respiratory mechanical impedance (Zrs) in unsedated sleeping infants in the first 3 days of life. Methods: Zrs was measured during 30‐s epochs of quiet sleep in term neonates born via spontaneous vaginal delivery with a non‐invasive FOT between 8 and 48 Hz. Total respiratory resistance (R), compliance (C) and inertance (I) were obtained by fitting Zrs spectra. Cluster analysis was used to determine a set of minimal Zrs spectra representing optimal respiratory mechanics for each infant. Results: Successful measurements were obtained in each of the first 3 days in 30/38 (78.9%) neonates. Group mean (± SD) values of R, C, I, and resonant frequency pooled for the 3 days were 45.9 ± 16.6 hPa s L −1, 0.97 ± 0.21 ml hPa −1, 0.082 ± 0.031 hPa s 2  L −1 and 19.2 ± 3.2 Hz, respectively. Within‐session variability represented by coefficient of variation was 5.34 ± 3.18% for R and 13.80 ± 8.57% for C. Greater between‐session variability was observed for the individual infants; however, the only statistically significant change over time was a 13% increase in R from day 1 to day 2. Parameter interdependence was significant (r 2  = 0.63) between R and I reflecting the large contribution of the upper airways to the total Zrs. Conclusions: Noninvasive measurement of Zrs can be made in neonates during natural sleep with a high success rate, even in the first hours of life.Pediatr Pulmonol. 2015; 50:344–352. © 2014 Wiley Periodicals, Inc.